Adult Asthma Consensus Guidelines Update 2003 - Catherine Lemière; Tony Bai; Meyer Balter; Charles Bayliff; Allan Becker; Louis-Philippe Boulet; Dennis Bowie; André Cartier; Andrew Cave; Kenneth Chapman; Robert Cowie; Stephen Coyle; et al. (Canadian Respiratory Journal)
BACKGROUND: Several sets of Canadian guidelines for the diagnosis and management of asthma have been published over the past 15 years. Since the last revision of the 1999 Canadian Asthma Consensus Report, important new studies have highlighted the need to incorporate new information into the asthma guidelines.